Functional ectodomain of the hemagglutinin-neuraminidase protein is expressed in transgenic tobacco cells as a candidate vaccine against Newcastle disease virus. - Kok, Song Lai; Yusoff, Khatijah; Mahmood, Maziah (Springer Verlag, 2013)
Recently, the use of plants for the production of recombinant proteins has been well demonstrated with promising outcomes. In this study, an efficient Nicotiana tabacum L. cv. Bright Yellow 2 (BY-2) cells system expressing the ectodomain of hemagglutinin-neuraminidase (eHN) protein from Newcastle disease virus (NDV) strain AF2240 was established. Transgenic tobacco BY-2 cell cultures expressing the immunogenic eHN protein were generated and the translation efficiency of eHN protein was enhanced using the 5′-untranslated region of Nicotiana tabacum alcohol dehydrogenase gene (NtADH 5′-UTR) under the control of strong cauliflower mosaic virus (CaMV 35S) promoter. Transgenic lines verified by real-time PCR showed high level of eHN mRNA transcripts and immunoblotting confirmed the presence of 66 kD eHN protein. The eHN protein was stably produced in an average of 0.2–0.4 % total soluble protein. Green fluorescent protein-tagged eHN protein was expressed and localized at the cytosol of BY-2 cell. All mice receiving purified eHN protein from transgenic tobacco BY-2 cells produced specific anti-NDV antibodies. We concluded that plant made eHN elicit immune response and can serve as candidate vaccine against NDV.